Divergent evolution of hemipenial morphology in two cryptic species of mainland anoles related to Anolis polylepis - Köhler, Johannes; Hahn, Martin; Köhler, Gunther (Salamandra, 2012)
Divergent evolution of hemipenial morphology between closely related forms appears to be a common phenomenon in mainland anoles. We discuss possible evolutionary scenarios for this finding, based on different lines of evidence from our work on Anolis polylepis and A. osa from southern Costa Rica. Molecular analysis suggests a very recent separation of these two forms and the occurrence of hybridisation in their contact zone. Evidence from crossbreeding experiments supports these assumptions. The results of an examination of female cloacal morphology indicate co-evolution of male and female genital morphologies and thereby contradict functional neutrality of hemipenial morphology.